Proporcingumo principo taikymas administracinėje ir aplinkos teisėje - Danėlienė, Ingrida (Teisė, 2009)
Straipsnyje nagrinėjami klausimai, susiję su proporcingumo principo samprata, šio principo reikšme ir vieta administracinėje teisėje bei konkrečioje valstybės valdymo srityje – aplinkos apsaugos teisiniuose santykiuose. Siekiama nustatyti, kokia proporcingumo principo taikymo praktika Europos Sąjungos bei vienos iš Europos Sąjungos narių – Lietuvos Respublikos – aplinkos teisėje ir šią teisę taikančioje teismų praktikoje. Ieškoma atsakymo į klausimą, kokie teisiniai gėriai, vadovaujantis proporcingumo principu, turi būti sveriami administracinėje ir aplinkos teisėje bei kuo šiuo aspektu svarbus proporcingumo ir atsargumoprincipo santykis.The article analyses issues relating to the principle of proportinality, the importance and the place of this principle in administrative law and, specifically, in one of the spheres of state administration – in the legal relations of environmental protection. The aim of the article is to establish the patterns of the application of the principle in the environmental law and the court practice of the European Union and in the Republicof Lithuania, which is a member state of the European Union. The article seeks to answer the question, which legal values are to be weighed on the proportionality scale in administrative and environmental law, also identify the relation of the proportionality and precautionary principles in this context.